The Influence of Learning Activity, Learning Habits, Learning Facilities, Peers, and Parental Support on the Learning Achievement of Grade X and XI Students in Tax Subjects at State Vocational School I Kinali, West Pasaman Regency - Emalia Putri; Yosi Eka Putri; Meri Rahmania (Journal of Classroom Action Research, 2025)
: This study aims to analyze the influence of learning activities, learning habits, learning facilities, peer support, and parental support—both partially and simultaneously—on the academic achievement of Grade X and XI students in the Tax subject at SMK Negeri 1 Kinali, West Pasaman Regency. The study employed a quantitative associative approach. The population consisted of 94 students from grades 10 and 11, and a total sampling technique was used, making the entire population the sample. Data were collected through questionnaires and analyzed using multiple linear regression with SPSS and EViews. Hypothesis testing was conducted using t-tests (partial) and F-tests (simultaneous) at a significance level of α = 0.05. The results showed that all five independent variables had a positive and significant effect on student academic achievement. Specifically, learning activities (coefficient 0.318; t = 7.126), learning habits (0.129; t = 5.370), learning facilities (0.408; t = 8.378), peer support (0.188; t = 3.361), and parental support (0.302; t = 3.563) all contributed positively. Simultaneously, these variables also had a significant effect, with an F-value of 59.396 > F-table (2.32) and a significance level of 0.000. In conclusion, both internal factors (learning activities and habits) and external factors (facilities, peers, and parental support) play a crucial role in improving students' academic achievement. Therefore, efforts to enhance student outcomes should be comprehensive, focusing on optimizing learning behaviors and strengthening support from the school environment, peers, and family.